ISOLASI DAN SELEKSI BAKTERI SEBAGAI AGEN BIOREMEDIASI LIMBAH CAIR PABRIK KAYU PUTIH - Tri Rahayuningsih; Umi Isnatin; Parwi Parwi (Universitas Merdeka Madiun, 2018)
This study aims to isolate and select bacteria as a bioremediation agent for wastewater of cajeput factory. The waterwaste of cajuput factory has not been utilized for liquid organic fertilizer because it still contains cajeput oil (phenol compound) which can disrupt plant growth. Therefore it is necessary to look for bacteria that have the ability to integrate of management waterwaste. Waterwaste samples is taken by random sampling in tri locations, namely the initial shelter, the second shelter and the waste disposal area. Bacteria are developed in liquid media, then isolated and identified on solid media. Identification of bacteria based on colony morphology, cell morphology and biochemical testing. Phenol degradation test was carried out using a completely randomized design with tri replications. Treatment of types of bacterial isolates namely B0 = Control, B1 = Bacillus, B2 = Psedomonas, B3 = Flavobacterium. The results showed that there were tri bacterial isolates found in wastewater of cajuput factory namely Bacillus sp, Pseudomonas sp and Flavobacterium sp. The highest amount of bacterial colonies was found in waste shelters of 2.41 x 106 colonies. The most effective bacteria in degrading phenol is Pseudomonas sp